Identification of The Determinants of Enterpreneurial Success: A Multidimensional Framework - Dyan Vidyatmoko; Pudji Hastuti (STI Policy and Management Journal, 2017)
Although the academics have discussed various topics related to the factors that influence the entrepreneurial success, but there are still many differences about which factors are very important. The most important characteristics of successful entrepreneurs often become a big question.  It is reasonable due to the increasing diversity of approaches used in a variety of disciplines on the study of entrepreneur. There were many literatures that discussed a variety of variables affecting the success of entrepreneurs, especially in developed countries. In an effort to fill the lack of research on the success of entrepreneurs in developing countries, especially in Indonesia,this paper tries to propose a theoretical framework to examine factors that affect the success of entrepreneurs,the proposed framework uses a multidimensional analysis of success factors whereby three factors are discussed simultaneously. These include the entrepreneur, the entrepreneurial firm and the external environment. Success is represented by three indicators which consist of employment growth, profitability and survival. This framework is the development of theoretical framework proposed by Kiggundu, and Lussier and Halabi. Compared to Kiggundu and Lussier and Halabi model, the proposed approach is expected to provide a comprehensive analysis of the factors affecting the success of entrepreneur in Indonesia. This multidimensional approach can illustrate the scope of various entrepreneurial phenomena in Indonesia.In addition, using the analytical technique to be used to test the relationship and the influence of independent variables, the concept of this framework will produce determinant variables and eliminate the variables that are not relevantThe study will use Structural Equation Model. It is relevant and useful both from the academic and practical points of view and has practical implications for policymakers in terms of conceptualizing and operationalizing factors affecting the success of entrepreneurs in Indonesia.